2000
DOI: 10.1007/s004200050017
|View full text |Cite
|
Sign up to set email alerts
|

Dermal absorption of N , N -dimethylacetamide in human volunteers

Abstract: DMAC vapor was significantly absorbed through the skin. Estimated NMAC values indicate that 20 mg/g x Cr NMAC seems to be appropriate as the biological exposure index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
4
20
0
Order By: Relevance
“…The present findings that no significant health effect was detected by the various tests among the 14 workers exposed to NMP at a maximum level of 0.8 ppm and below might provide additional evidence to support the current OEL value of 1 ppm for NMP recommended by JSOH 33) .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The present findings that no significant health effect was detected by the various tests among the 14 workers exposed to NMP at a maximum level of 0.8 ppm and below might provide additional evidence to support the current OEL value of 1 ppm for NMP recommended by JSOH 33) .…”
Section: Discussionsupporting
confidence: 71%
“…The urinary NMP levels with reference to the concentrations of exposure to NMP were found to be higher in this study than in Bader et al's study 26) . Nomiyama et al 33,34) suggested that the greater urinary biological monitoring values of N,N-dimethylformamide and N,N-dimethylacetamide, both of which are enhanced skin penetrators, in the occupational setting than in the experimental setting are due to the workload, which would increase both the respiratory volume and sweating, leading to the increased percutaneous penetration of these solvents. Second, in sharp contrast to Bader et al's study 26) , no positive correlation between the NMP exposure and urinary NMP levels could be established in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The dermal absorption (%) here ranged wider and was a little higher than previous data, 14±39% (Max®eld et al 1975) and13±36% (Mra z andNohova 1992), both obtained on four volunteers. This kind of wide variation on each individual was also observed with DMAC, and might be due to some other, personal factors (Nomiyama et al 2000).…”
Section: Resultsmentioning
confidence: 93%
“…The half-life of urinary NMF from dermal exposure, 4.75 1.63 h (range: 2.1±7.0 h), was signi®cantly longer than that from respiratory exposure, 2.42 0.63 h (range: 1.2±3.2 h). This dierence between the two half-lives of the urinary metabolite after dermal and respiratory exposures was also observed in N,Ndimethylacetamide (DMAC) in spite of the insigni®-cance of the dierence (Nomiyama et al 2000). Percutaneous absorption would entail a transfer from the surface of the skin to blood vessels in the dermis through the epidermis including stratum corneum.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation